Immediate Postoperative Imaging Following Elective Lumbar Fusion Provides Little Clinical Utility. Issue 14 (15th July 2021) - Ronald, Andrew A.; Herring, Eric Z.; Gerges, Christina; Shost, Michael; Jella, Tarun; Sajatovic, Martha; Labak, Collin M.; Smith, Gabriel
Abstract : Study Design: Retrospective review at a single institution of all adult patients who underwent elective lumbar fusion surgery for degenerative spinal disease from 2013 to 2018. Reoperation rates and change in clinical management due to routine imaging findings were the primary outcomes. Objective: To investigate what effects immediate routine postoperative imaging has on the clinical management of patients following lumbar fusion surgery. Summary of Background Data: The clinical utility of routine postoperative imaging following lumbar fusion surgery remains uncertain. Existing studies on the clinical utility of postoperative imaging in lumbar fusion patients have largely focused on imaging obtained post-discharge. We present a retrospective analysis that to our knowledge is the first study reporting on the clinical utility of routine imaging in lumbar fusion patients during the immediate postoperative period. Methods: The medical records of patients who had undergone elective lumbar instrumented fusion for degenerative disease from 2013 to 2018 by neurosurgeons across one regional healthcare system were retrospectively analyzed. Inpatient records and imaging orders for patients were reviewed. Routine immediate postoperative imaging was defined by any lumbar spine imaging prior to discharge in the absence of specific indications. Results: Analysis identified 115 patients who underwent elective lumbar instrumented fusion for degenerative disease. One-hundred-twelve patients received routine postoperative imaging. Routine imaging was abnormal in four patients (4%). There was one instance (<1%) where routine immediate postoperative imaging led to change in clinical management. Abnormal routine imaging was not associated with either reoperation or development of neurological symptoms postoperatively ( P = 0.10), however, new or worsening neurologic deficits did predict reoperation ( P < 0.01). Conclusion: New neurologic deficit was the only significant predictor of reoperation. Routine imaging, whether normal or abnormal, was not found to be associated with reoperation. The practice of routine imaging prior to discharge following elective lumbar fusion surgery appears to provide little utility to clinical management. Level of Evidence: 3 Abstract : The clinical utility of routine postoperative imaging following lumbar fusion surgery remains uncertain. The medical records of patients who had undergone elective lumbar instrumented fusion for degenerative disease were retrospectively analyzed. Routine imaging, whether normal or abnormal, was not found to be associated with reoperation.